Particle size and metal composition of gouging and lancing fumes - Keyter, Marelé; Van Der Merwe, Alicia; Franken, Anja (Journal of occupational and environmental hygiene, 2019)
Metal gouging and lancing liberate particles of an unknown size and composition. Fumes are formed when vaporized materials condense in air, creating fine and ultrafine particles which can agglomerate. Particle sizes may be <1 µm in diameter. Inhalation of this mixture of metal fumes can lead to adverse health effects. This study characterized fumes by particle size fractions and metal composition. As particles may be in the submicron range, the nano-size fraction was included. Randomized, side-by-side area samples of fumes liberated during gouging and lancing were collected. Samplers included the conductive plastic Institute of Occupational Medicine (IOM) samplers (inhalable fraction), GK2.69 stainless steel thoracic cyclones (thoracic fraction), aluminum respirable cyclones (respirable fraction), Nanoparticle Respiratory Deposition (NRD) samplers (nano-size fraction), and open-face filter cassettes (particle size distribution-PSD). Samplers were mounted at a height of between 1.3 m and 1.7 m, in the worst-case scenario area (down-wind). Forty-six samples were collected during gouging and 26 during lancing. Mass concentrations per fraction ranges (excluding nano-size) were found to be 1.27-17.27 mg/m 3 (inhalable), 1.83-13.96 mg/m 3 (thoracic) and 0.88-15.82 mg/m 3 (respirable) for gouging; and 2.34-5.60 mg/m 3 (inhalable), 2.82-4.01 mg/m 3 (thoracic), and 1.89-3.24 mg/m 3 (respirable) for lancing. PSD analysis confirmed the presence of nano-size particles with a mean size of 171.76 (±56.27) nm during gouging and 32.33 (±7.17) nm during lancing. Inductively Coupled Plasma Mass Spectrometry (ICP-MS) analysis of samples indicated the presence of chromium (Cr), copper (Cu), iron (Fe), manganese (Mn), molybdenum (Mo), nickel (Ni), and tin (Sn) in the respective particle size fractions (including nano-size) of both processes. Negative health effects associated with metal inhalation are well known, while nanoparticles' unique properties enable them to cause further detrimental health effects. The nano-size fraction should be included in personal exposure assessments and control measures.